Wajah Undang-undang Keter (Tutup) Bukaan Informasi Publik di Indonesia - Endang Widuri (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
On April 3rd 2008, DPR enacted Act Number 14 about Disclosure Public Information (UU KIP). This act aimed toinstitutionalize law framework for public right fulfillment to access power implementation process. The main object of this act isfreeing everyone from everything negative caused by a government reticence. People should free to participate in policymaking, free from corruption and human rights violence. Therefore, Disclosure Public Information Act is very important,because information is main resource for everyone to participation in government activity. Without information, people can’tuse his right and duty maximally as citizen